Peranan Notaris dalam Program Pemerataan Investasi Dalam Undang-Undang Cipta Kerja - as, fariz; Santika, Ida Bagus Agung Putra; Buana Rumiartha, I Nyoman Prabu (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 9 No 02 (2024), 2024)
The purpose of this writing is to understand the construction of norms in the Job Creation Law (UU Cipta Kerja) concerning the principle of equity, particularly regarding share ownership, which has traditionally been dominated by foreigners or the upper-class society. The government has placed more emphasis on Micro and Small Enterprises to balance investment and create an investment climate that benefits society equally. Therefore, regulation of share ownership in the Job Creation Law is necessary to ensure that the process of equity is implemented. Before that, to achieve equitable investment implementation not yet regulated by the Job Creation Law, notaries as public officials play a role in the investment equity program under the Job Creation Law. This legal research method uses normative legal research, examining the norms of the Job Creation Law concerning share ownership. The research findings indicate that the ideal concept of the Job Creation Law is to provide regulations prioritizing share ownership for the community, including criteria such as actors in Micro and Small Enterprises (UMK), those in areas of natural resource exploitation zones, and individuals with minimal investment funds. This is to align with the principles of the Job Creation Law and harmonize with the Pancasila and the 1945 Constitution of the Republic of Indonesia, which mandates welfare for all Indonesian citizens. Notaries, as public officials, have a role in achieving the investment equity program of the Job Creation Law, specifically through drafting deeds, providing legal counseling, and/or conducting legal discovery that is concretized in deeds